Socioeconomic factors and sex effects of postpartum maternal depression on offspring internalizing symptoms: a systematic review and meta-analysis - Yang Geng; Wenlan Liu; Zhiying Yu; Hui Zhang; Yun Li; Weihua Zhao (BMC Medicine)
Abstract Background Postpartum maternal depression and socioeconomic factors are established risk factors for the mental health of offspring. It has been consistently unclear as to whether female or male offspring are more vulnerable to the effects of postpartum maternal depression at different stages of the child’s life course. To determine whether the characteristics of postpartum maternal depression with a history of prenatal depression influence sex differences in offspring internalizing symptoms across childhood and adolescence, socioeconomic factors should be considered. Methods We systematically searched PubMed, Embase, PsycINFO, CNKI, and SinoMed databases from inception to November 28, 2023, and selected longitudinal cohort studies that quantified sex differences in internalizing symptoms of children and adolescents. Pooled standardized mean differences (SMDs) were calculated using random-effects models. ROBINS-E tool was used to rate the quality of evidence. Results Twenty-eight studies were eligible between 1997 and 2023, including 24,022 mother–child dyads. Sex-difference trajectories of offspring internalizing symptoms were identified after exposure to postpartum maternal depression, ranging from a lack of significant sex differences in childhood to a higher prevalence observed among girls than boys in adolescence (SMD, 0.25, 95% CI, 0.13–0.38). Economic income and maternal education affected the associations between the magnitude and concurrent recurrence of postpartum depression and significant sex differences in adolescent internalizing symptoms, respectively. After adjusting for socioeconomic factors, early nonconcurrent recurrence of postpartum depression was associated with greater odds of internalizing symptoms among adolescent girls than among boys (β = 0.03, 95% CI, 0.01–0.06); however, there was no statistical significance after adjusting for prenatal depression. Conclusions Socioeconomic factors differentially impacted the association between postpartum maternal depression and significant sex differences in adolescent internalizing symptoms. Independent of socioeconomic factors and prenatal depression, postpartum maternal depression was not associated with significant sex differences in adolescent internalizing symptoms. Therefore, the significant sex effects of postpartum maternal depression are more likely due to complex interactions between maternal depression and the intrauterine and postpartum environments that shape offspring sex-difference trajectories, with consequences occurring for later internalizing symptoms in adolescence. Trial registration PROSPERO, CRD42022301445.